Electric Vehicles Home Charging Impact on a Distribution Transformer in a Portuguese Island - Godina, R.; Paterakis, N. G.; Erdinc, O.; Rodrigues, E. M. G.; Catalao, J. P. S. (IEEE, 2015)
This paper analyses the impact of the high penetration of electric vehicles (EVs) charging loads on the thermal ageing of distribution transformers of an isolated electric grid in a Portuguese Island. In this paper, a transformer thermal model is used to estimate the hot-spot temperature (theta(h)) given the load ratio. Real data are used for the main inputs of the model, i.e. residential load, transformer parameters, time-of-use rates and electric vehicle parameters. Conclusions are duly drawn.
Keywords: distribution transformer; EV charging; loss-of-life; battery; transformer ageing; HIGH PENETRATION; SYSTEMS; LIFE; DEMAND; LOAD; Computer Science; Engineering